PENGUATAN ORGANISASI POKDARWIS SEBAGAI UJUNG TOMBAK PENGEMBANGAN WISATA KAMPUNG PELANGI KOTA SEMARANG - Eko Punto G (Departemen Linguistik, Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
AbstractKampung Pelangi is a result of the thematic village development program launched by the Semarang City Government, with a focus on tourist villages. Kampung Pelangi is already well known by the public both at home and abroad. Tourism Awareness Group (Pokdarwis) is an organization that should actively develop integrated tourism village activities, but the current conditions have not been able to work well. Therefore, organizational improvement and strengthening is needed so that this tourist village can develop sustainablyKeywords : kampung pelangi, wisata, pokdarwis, semarang